(untitled) (Research, Society and Development, 2022)
Introduction: From the emergence of the new coronavirus known as COVID-19 and its geographical distribution, the WHO declared that the world was experiencing a pandemic. At the same time, the academic year of residencies in the health area began throughout Brazil, bringing the need to adapt programs to the guidelines of government agencies on the pandemic. Initially, there were professional guidelines for nutritionists to work remotely, which were changed with the evolution of knowledge about the virus, vaccination and access to PPE, allowing residents to enter to care for patients admitted to the COVID-19 ICU. Objective: This report aims to present the experience lived in the COVID-19 ICU from the perspective of a nutritionist resident, taking stock of the work of professionals, patient care and family care. Method: This is an experience report that presents the balance of the experience lived by a nutritionist resident in the COVID-19 ICU scenario between March and May 2021, based on legal documents and articles found in Pubmed, Scielo and Academic Google, divided into themes related to the performance of the resident nutritionist. Results and discussion: The work is divided into four themes, dealing with residency in the context of the pandemic, the insertion of the resident in the COVID ICU in the occurrence of the 2nd wave, the role of the resident nutritionist in this scenario and the fruits harvested in this experience. Final considerations: It is concluded that the balance of work left a lot of wear, despite the experience gained and that reflections on in-service training in the residency format are necessary.